The construction of a Juridical Ontology - Alves, Isa (2009)
Domain ontologies are important resources in several tasks related to the language processing, especially in those related to information retrieval and extraction in textual bases. A proposal for an ontological structuring of verbs belonging to the juridical domain is presented here aiming at improving Natural Language Processing (NLP) systems, and more specifically, information retrieval systems of the Department of Justice of Portugal. In order to do so, we present a methodology that is an integrated representation of the verbal content from the perspective of the Formal or Logic Semantics, Lexical Semantics, Grammatical Semantics and Pragmatics heading for the construction of an ontology. Approaches such as logic-semantic relationships, semantic roles and frames were more productive for the construction of the ontology proposed.